Perancangan Rem Linier Memakai Fluida MR dengan Kendali Arus Listrik Berbasis Fungsi Linier - Estiko Rijanto; Aditya Sukma Nugraha; Arif Sugiharto; Rifa Rahmayanti; Sapdo Utomo (Jurnal Rekayasa Elektrika, 2017)
Magneto rheological (MR) fluid has been used in various electro mechanical devices since it has advantages of being able to be controlled by external magnetic force. However, application of the MR fluid for linear brakes is still scarce. This article proposes a new design of linear MR brake. It has multiple magnetic poles, and its core can be connected in series inside the piston. Equations which express relationships between mechanical force and magnetic force as well as magnetic force and electric current have been derived. As a result, a polynomial function was obtained which expressed mechanical force of the brake as a function of electric current. Parameter values of geometric dimension and magnetic permeabilities of components were substituted into the equation, and a control law is proposed to control the brake force by manipulating current using the inverse of a linear function. When electric current of 1 A was supplied into the coil, brake force of 111.4 Newton was obtained. Various values of brake force can easily be realized by controlling electric current based on the derived linear function control law.